Survey on Improving Wireless Sensor Network (WSN) with Li-Fi and Wi-Fi for Smart City Applications - Parmar, Karan. A; Patel, D.M; Thakore, D.G (International Journal of Computer Sciences and Engineering, 2019)
The need of seamless and ceaseless faster internet connection speed is on the rise. Since, most of us have access to Wireless Fidelity (Wi-Fi) to fulfill this need, which can become our only option. That’s why, in 2011, a new revolutionary technology comes into light, which is known as, Light Fidelity (Li-Fi). But, testify existing Li-Fi system, a detailed study of its behavior with other IEEE standards such as, Low power Bluetooth (BLE), Wi-Fi, ZigBee etc. should done, which can fulfill by Wireless Sensor Network (WSN). This survey paper represents numerous work happened in field of Wireless Sensor Networks (WSNs) from various IEEE standard based protocols like, Wi-Fi and Li-Fi. So, here at first, brief introduction of various IEEE standards and Wireless Sensor Network (WSN) carried out. Then, in next section, a literature review of various research paper presented along with comparison between Li-Fi and Wi-Fi technologies and applications of Li-Fi in Wireless Sensor Network.